2011
DOI: 10.1002/adfm.201100784
|View full text |Cite
|
Sign up to set email alerts
|

Routes to Achieving High Quantum Yield Luminescence from Gas‐Phase‐Produced Silicon Nanocrystals

Abstract: Plasma‐synthesized silicon nanocrystals with alkene ligands have shown the potential to exhibit high‐efficiency photoluminescence, but results reported in the literature have been inconsistent. Here, for the first time, the role of the immediate post‐synthesis “afterglow plasma” environment is explored. The significant impact of gas injection into the afterglow plasma on the photoluminescence efficiency of silicon nanocrystals is reprorted. Depending on the afterglow conditions, photoluminescence quantum yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
110
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(114 citation statements)
references
References 26 publications
(25 reference statements)
4
110
0
Order By: Relevance
“…The reactor is a Pyrex tube through which silane diluted with a carrier gas is decomposed to form Si-NCs. A detailed description for the synthesis of the LIDD Si-NCs has been reported earlier, 27 so only the important features will be covered here. To prepare the LIDD Si-NCs, hydrogen gas was injected into the afterglow of the plasma and additional synthesis conditions are outlined in Table I.…”
Section: Methodsmentioning
confidence: 99%
“…The reactor is a Pyrex tube through which silane diluted with a carrier gas is decomposed to form Si-NCs. A detailed description for the synthesis of the LIDD Si-NCs has been reported earlier, 27 so only the important features will be covered here. To prepare the LIDD Si-NCs, hydrogen gas was injected into the afterglow of the plasma and additional synthesis conditions are outlined in Table I.…”
Section: Methodsmentioning
confidence: 99%
“…4,5 Also improvements in luminescent quantum yield of ncSi through surface-capping control, [6][7][8] makes them interesting for quantum dot applications. The synthetic strategies for making ncSi have been recently summarized by Mangolini.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that surface quality of nanostructures has a significant influence on related device performance. Several pioneer works on Si NC-based device have shown that the performance can be further improved through proper Si NCs surface treatment [35][36][37][38]. In this work, we demonstrate that controlled particle oxidization can be employed as an easy and effective way for surface passivation.…”
Section: Introductionmentioning
confidence: 88%